Analisis IKM untuk Mengukur Kepuasan Masyarakat dalam Meningkatkan Kualitas Pelayanan Dinas Kearsipan dan Perpustakaan Provinsi Jawa Tengah - Anggelina, Cindi Claudi; Raharjo, Teguh Hardi (Jurnal EMT KITA, 2025)
This study aims to analyze the Community Satisfaction Index (IKM) in measuring the level of satisfaction with the quality of services provided by the Archives and Library Office of Central Java Province. The research focuses on examining the nine elements of IKM, namely: requirements, systems and procedures, completion time, service fees, service type product specifications, implementer competence, implementer behavior, facilities and infrastructure, and complaint handling. This research employed a quantitative method with a survey approach, where data were collected using a Likert scale-based questionnaire. The analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the Confirmatory Factor Analysis (CFA) method to assess construct validity and the relationship between each variable and public satisfaction. Furthermore, hypothesis testing was carried out to determine the partial significant effects of each element on public satisfaction. The results of the CFA analysis indicate that the IKM model as a whole has good construct validity, with significant variables forming latent factors for each service element. Of the nine proposed hypotheses, 4 were accepted: the variables of service time and service-specific product type showed a positive and significant effect on public satisfaction. Meanwhile, 5 hypotheses were rejected namely, the variables of requirements, procedures, costs, implementer behavior, and facilities and infrastructure although they had a positive but not significant effect on public satisfaction. The model fit analysis through the goodness-of-fit test confirmed that the IKM model is suitable for application in the context of public services within the Archives and Library Office of Central Java Province. These findings underscore the importance of continuous implementation and evaluation of IKM elements to improve the quality of public services that are adaptive and oriented toward community needs.
Keywords: Community Satisfaction Index (IKM); Public Satisfaction; Service Quality